MODEL OF MAGNETIC DEGENERATE DWARF - Smerechynskyi, S. V.; Dzikovskyi, D. V. (Одеські астрономічні публікації, 2017)
The macroscopic characteristics of the degenerate dwarves were calculated based on the equation of state of a spin-polarized electron gas at T = 0K as well as at ﬁnite temperatures. It was shown that the spin-polarization cause an increase of the radius and mass in comparison with the characteristics of standard Chandrasekhar model. Within adopted model, the value of critical mass was estimated, by which an instability due to general relativity eﬀects occurs. Parameters of model are: the relativistic parameter x0 at stellar center, the chemical composition parameter µe = ‹A/Z›, the degree of spinpolarization ζ, the dimensionless temperature of core T0∗ = kBTc/m0c2 and its radius ξ0 = Rc/R (Rcis the core radius, R is the radius of a dwarf). The inverse problem for a sample of massive dwarfs was solved using the known masses and radii and the parameters x0, T0∗ were found for ﬁxed values of spin-polarization.